Asymptomatic carriage and molecular characterization of Staphylococcus aureus in pre-clinical and clinical medical students - Brodíková, Kristýna; Rezková, Bohdana; Koláčková, Ivana; Karpíšková, Renáta (Folia microbiologica, 2025)
Medical students are exposed to the hospital environment and patients during their studies, increasing the risk of exposure to virulent and antibiotic-resistant isolates of Staphylococcus aureus. The aim of the study is to determine the prevalence of Staphylococcus aureus among medical students who have varying levels of exposure to the hospital environment to provide valuable insights into the risk of colonization and transmission. Nasal swabs and fingerprints were obtained and cultured on a selective medium for staphylococci. The obtained isolates were confirmed as methicillin-sensitive S. aureus (MSSA) or methicillin-resistant (MRSA) using PCR. Antibiotic resistance, the presence of virulence genes including enterotoxin encoding genes, and spa typing were performed. Among pre-clinical students, MSSA was detected on the nose in 45.2% and on the fingerprints in 10.6% of the participants. Among clinical students, MSSA was detected on the nose in 42.0% and on the fingerprints in 25.4%. Only one MRSA isolate was obtained. Genes seg and sei were the most frequently detected in both student groups, with their presence in over 40% of isolates among clinical students. The eta and etb genes were mainly detected from the nose in both student groups. In pre-clinical students, S. aureus carrying eta gene occurred in 6.4% and etb in 8.5%. In clinical students, the occurrence was 5.1% for eta and 8.5% for etb. The tst gene was identified only in the nose and fingerprints of the clinical student group. The most frequently observed resistance was to clindamycin and erythromycin. In total 58 different spa types were identified. High rates of asymptomatic MSSA carriage were observed in both groups of medical students. Detected MSSA strains showed a high degree of genetic variability, with a number of them carrying the virulence and antibiotic resistance genes. Although students do not exhibit increased risk to their patient's, increased hygiene is required in asymptomatic carriage personnel. The overall prevalence of MRSA was low, with a minimal risk of spread.
Keywords: methicilin rezistentní Staphylococcus aureus; asymptomatické infekce; Students, Medical; lidé; přenašečství; Adult; MRSA; Medical students; Nose; bakteriální léková rezistence; antibakteriální látky; Virulence Factors; Female; Prevalence; Asymptomatic Infections; Humans; nos; Anti-Bacterial Agents; Microbial Sensitivity Tests; mikrobiální testy citlivosti; Spa type; Drug Resistance, Bacterial; mužské pohlaví; studenti lékařství; mladý dospělý; ženské pohlaví; prevalence; Young Adult; Virulence genes; Antibiotic resistance; Male; Carrier State; faktory virulence; dospělí; Staphylococcal Infections; Staphylococcus aureus; stafylokokové infekce; Methicillin-Resistant Staphylococcus aureus